New Alternatives to Milk From Pulses: Chickpea and Lupin Beverages With Improved Digestibility and Potential Bioactivities for Human Health - Duarte, Carla Margarida; Mota, Joana; Assunção, Ricardo; Martins, Carla; Ribeiro, Ana Cristina; Lima, Ana; Raymundo, Anabela; Nunes, Maria Cristiana; Ferreira, Ricardo Boavida; Sousa, Isabel (Frontiers in Nutrition, 2022)
There is a strong demand for plant-based milk substitutes, often low in protein content (< 1.5% w/v). Protein-rich pulse seeds and the right processing technologies make it possible to make relevant choices. The major objective of this work was to assess the impact of processing on the nutritional characteristics of beverages with a high impact on health, in particular on digestibility and specific bioactivities. The results suggest that pulse beverages are as high in protein content (3.24% w/v for chickpea, and 4.05% w/v for lupin) as cow’s milk. The anti-nutrient levels characteristic of pulses have been considerably reduced by a strategic processing. However, when present in small quantities, some of these anti-nutritional factors may have health benefits. Controlling processing conditions plays a crucial role in this fine balance, as a tool to take advantage of their health benefits. There was evidence of protein hydrolysis by in vitro digestion and limited bioaccessibility of minerals. In addition to being highly digestible, lupin and chickpea beverages had anti-inflammatory and anti-carcinogenic potential evaluated through the inhibition of metalloproteinase MMP-9.